2020
DOI: 10.1038/s41419-020-2270-1
|View full text |Cite
|
Sign up to set email alerts
|

miR-210-5p promotes epithelial–mesenchymal transition by inhibiting PIK3R5 thereby activating oncogenic autophagy in osteosarcoma cells

Abstract: Osteosarcoma (OS) is a malignant bone tumor which occurs mainly in adolescents with frequent pulmonary metastasis and a high mortality rate. Accumulating evidence has indicated that microRNAs (miRNAs) play a vital role in various tumors by modulating target genes as well as signal pathways, and aberrant expression of miRNAs may contribute to OS progression. This study aimed to determine the association between miR-210-5p expression and OS progression and to investigate its potential underlying mechanism. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 62 publications
4
42
0
Order By: Relevance
“…miR-210-3p is the guide-strand that integrates into the RISC (RNA induced silencing complex), whereas miR-210-5p is the passenger-strand that is inactivated through degradation [ 19 , 20 ]. miR-210-5P is up-regulated in several malignant tumors that are associated with a variety of functionally important targets involved in cancers [ 21 ]. However, whether miR-210-5p could regulate mitophagy to participate in drug-sensitivity remains to be examined in depth.…”
Section: Introductionmentioning
confidence: 99%
“…miR-210-3p is the guide-strand that integrates into the RISC (RNA induced silencing complex), whereas miR-210-5p is the passenger-strand that is inactivated through degradation [ 19 , 20 ]. miR-210-5P is up-regulated in several malignant tumors that are associated with a variety of functionally important targets involved in cancers [ 21 ]. However, whether miR-210-5p could regulate mitophagy to participate in drug-sensitivity remains to be examined in depth.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the effect of autophagy on metastasis, as observed by Zhang et al [ 35 ], and Liu et al [ 36 ]. In contrast, Liu et al found that microRNA-210-5p promotes metastasis by suppressing PIK3R5-induced autophagy via the mTOR pathway [ 37 ]. The differences in our conclusions may result from the method of autophagy inhibition: chloroquine suppresses autophagy by blocking autophagosome-lysosome fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, identifying core molecules associated with tumor proliferation and invasion is crucial for designing new treatment regimens. Increasing evidence unveils that miRNAs perform vital functions in OS progression (Fellenberg et al, 2019; Liu, Jiang et al, 2020; Wang, Shi et al, 2020). According to reports, miRNA containing Exos from OS encourage OS to proliferate and invade via controlling cell‐to‐cell communication in the local and remote microenvironment.…”
Section: Exo‐ncrnas In Osmentioning
confidence: 99%